Process improvement of the solid-subtrate fermentation of coconut (Cocos Nucifera L.) residue ; Sonia Y. De Leon, adviser. - Dumelod, Donna Delle J. (1993)
This study was done to improve the process of producing protein-enriched coconut residue flour (PECRF) through solid substrate fungal fermentation while cutting material and energy costs. The first phase involved the optimization of the substrate-to water ration and the pH level of the raw meterial--coconut residue--in the production of PECRF. Among the substrate to water ratios of 1:2, 1:1.5, 1:1 and 1:0.5, the ratio 1:1, gave the highest protein level at 31.1352% and thus selected for the second phase. The pH levels 4.0, 5.0 and the unadjusted pH (5.7) gave no significant effect on the protein contents of PECRF therefore removing the pH adjustment in the process. The second phase involved the optimization of the combinations of mineral supplements in the production of PECRF. The combination-abcde-containing H2NC13ONH2 (a), (NH4)2SO4 (b), KH2PO4 (c), MgSO4 . 7H20 (d) CaCl2 (e) gave the highest protein content at 30.1657% db. This was followed by abcd at 29.4712% at 28.6518%. Combination abc affected the lowest cost of mineral supplements added at P6.552/100 g coconut residue as compared to abcd's 7.156/100 g coconut residue without significant difference from abcde, thus was selected as the optimum mineral combination. The third phase involved the comparison of the protein content, microbial load and cost of production of PECRF from the modified process (MP) and the standard process (SP). The standard process involved a substrate-to-water ratio of 1:2, a pH of 5.0, and the use of the mineral combination abcde. The fermentation conditions of the modified process involved a substrate-to-water-ratio of 1:1 without adjusting the pH level and the use of the mineral combination abc. Protein analysis of the PECRF produced through the former showed a higher level of protein content at 29.890% while the level from that of the latter was 27.7137%. It was found that the both of these are significantly different from each other. The Total Plate count of the PRCRF (MP) is 3,041.67 CFU/g while that of the SP is 11,205.00 CFU/ml. The Yeast and Mold Count of the PECRF (MP) is 248.75 CFU/g while that PECRF (MP) per coconut residue is lower at P61.76 than that of the SP at P78.79.